MENINGKATKAN PERKEMBANGAN BAHASA ANAK MELALUI MEDIA DIORAMA DI TK DHARMA WANITA PERSATUAN 1 ASEMBAGUS SITUBONDO - Shofiyatul Layinah; Farhatin Masruroh (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2020)
The development of children's language in class B1 with 21 students is still a minority of children who still have difficulty in communicating even just to convey ideas or ideas they still feel embarrassed or afraid to convey it. Even when invited to talk with others they are still unable to respond properly. Based on the background of the problem, this research aims to find out the results of improving children's language development through diorama media at the TK Dharma Wanita Persatuan 1 Asembagus Situbondo. The type of research used is classroom action research by conducting a controlled investigation to find and solve learning problems in class. Problem solving is done in cycles, which consists of planning, action, observation, and reflection with the aim of improving the quality and learning outcomes in class. The results obtained from improving children's language development through media dioramas in TK Dharma Wanita Persatuan 1 Asembagus Situbondo in the first cycle reached 61.9% of students who were able to reach KKM from a total of 21 students and in cycle II it reached 90% meaning that of 21 students only there are 2 students who have below average ability.